2019
DOI: 10.3390/ijerph16020229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Walking in a Forest on Young Women

Abstract: The effects of forest activities on health promotion have received increasing attention. The aim of this study was to evaluate the physiological and psychological effects of brief walks in forests on young women. The experiments were conducted in 6 forests (test) and 6 city areas (control). Overall, 12 participants in each area (60 participants in total, mean age: 21.0 ± 1.3 years) were instructed to walk in a forest and a city area for approximately 15 min; simultaneously, their heart rate variability, heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
146
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(164 citation statements)
references
References 44 publications
14
146
3
1
Order By: Relevance
“…As Bowler et al (5) reported, 13 studies on the effects of walking in natural environments were published between 1991 and 2008, most of which reported that nature therapy decreased negative emotions, such as anger, fatigue, and sadness, and enhanced positive emotions, such as energy. The psychological benefits of forest-walking have been supported by many subsequent studies (6,7). However, the benefits of forest-walking are not only psychological.…”
Section: Introductionmentioning
confidence: 94%
“…As Bowler et al (5) reported, 13 studies on the effects of walking in natural environments were published between 1991 and 2008, most of which reported that nature therapy decreased negative emotions, such as anger, fatigue, and sadness, and enhanced positive emotions, such as energy. The psychological benefits of forest-walking have been supported by many subsequent studies (6,7). However, the benefits of forest-walking are not only psychological.…”
Section: Introductionmentioning
confidence: 94%
“…Numerous studies have demonstrated the effects of forests in mitigating stress states and inducing physiological relaxation in healthy individuals [7][8][9][10][11][12][13][14][15][16][17][18]. Walking through a forest and/or viewing sceneries can reduce levels of salivary cortisol, a stress hormone [7][8][9][10][11][12][13][14]17], blood pressure [8,11,12,15,17], and pulse rate [8,10,11,13,15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the effects of forests in mitigating stress states and inducing physiological relaxation in healthy individuals [7][8][9][10][11][12][13][14][15][16][17][18]. Walking through a forest and/or viewing sceneries can reduce levels of salivary cortisol, a stress hormone [7][8][9][10][11][12][13][14]17], blood pressure [8,11,12,15,17], and pulse rate [8,10,11,13,15,17,18]. It can also increase parasympathetic nervous activity, which is enhanced during relaxation [8,10,[12][13][14][15][16][17][18], and can suppress sympathetic nervous activity, which increases in stressful situations [8,[12][13][14][15]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…forest tenure reform, gender structure, household, off-farm employment, sustainable forest management 1 | INTRODUCTION Forestry is the basic industry, which produces tremendous economic, ecological, and social benefits (Fujii, Sato, & Managi, 2017;Mei & Clutter, 2012;Song, Ikei, Kagawa, & Miyazaki, 2019), and the benefit outputs mainly depend on continued forest management investment (Blanco et al, 2018;Robinson & Lokina, 2011;Widianingsih, Theilade, & Pouliot, 2016). Forest management is a typical traditional labor-intensive industry, and the labor force is regarded as the main productive factor of economic output and the major decision-making factor in forestry economic activities (Fisher, 2004;Peng, Deng, Zhang, Sun, & Xiong, 2019).…”
Section: Introductionmentioning
confidence: 99%